New Anticoagulant Agents: Incidence of Adverse Drug Reactions and New Signals Thereof - Treceño-Lobato, Carlos; Jiménez-Serranía, María-Isabel; Martínez-García, Raquel; Corzo-Delibes, Francisco; Martín Arias, Luis H. (Seminars in Thrombosis and Hemostasis, 2019)
The aim of this study was to evaluate the adverse drug reaction (ADR) incidence rate and new signals thereof for classic compared with new anticoagulants in real-life ambulatory settings. The authors performed an observational cross-sectional study in two cohorts of surveyed patients treated with vitamin K antagonists (VKAs; acenocoumarol or warfarin) or nonvitamin K antagonist oral anticoagulants (NOACs; apixaban, edoxaban, rivaroxaban, dabigatran etexilate). Descriptive, clinical, and ADRs data were reported and analyzed through a bivariate analysis (odds ratio [OR]) to compare the ADRs incidence rate and an adaptation of Bayesian methodology (false discovery rate [FDR] < 0.05) to detect new signals. A total of 334 patients were surveyed—average international normalized ratio (INR) of 2.6—and 45.4% taking new anticoagulants. Note that 835 ADRs were reported; 2.5 per patient (2.8 in the VKA cohort, 2.1 in the NOAC cohort). The authors obtained higher risk of epistaxis (OR, 2.18; 95% confidence interval [CI], 1.01–4.74) and hematoma (OR, 2.43; 95% CI, 1.39–4.25) with VKAs and lower risk of global bleeding symptoms with NOACs (OR, 0.45; 95% CI, 0.28–0.71). After standardizing the data, a significant risk of diarrhea with VKAs was observed (OR, 3.37; 95% CI, 1.09–10.41). They also detected an intense positive signal regarding the use of VKAs and osteoporosis (FDR < 0.001), specifically acenocoumarol (FDR < 0.002). NOACs presented lower risk of bleeding, especially dabigatran (FDR < 0.031), and of dermatological pathologies with apixaban being the safest (FDR = 0.050). The lower risk of global bleeding and a potential protective effect against osteoporosis in patients treated with NOACs postulate them as safer than VKAs.
Keywords: new oral anticoagulant; vitamin K antagonist; bleeding; osteoporosis